Do groundwater dynamics drive spatial patterns of tree density and diversity in Neotropical savannas? - Villalobos Vega, Randol (2014)
Questions: What are the temporal and spatial variations of groundwater depth along topographic gradients in Neotropical savannas? Are patterns of tree density and species diversity along topographic gradients in Neotropical savannas controlled by water table depth? Do soil and groundwater nutrient concentrations differ along topographic gradients in Neotropical savannas? Location: Fire-protected savannas of central Brazil. Methods: Over 16 mo, we monitored temporal and spatial variations in groundwater levels using automated submersible pressure transducers installed in ten wells located along two topographic gradients (five wells per gradient) of 950 m and 1703 m in length, representing elevations of 47 and 37 m a.s.l., respectively. We located the wells according to changes in vegetation physiognomies from woody savannas at high elevations, to open shrubby grasslands at low elevations. Along each topographic gradient we determined soil and groundwater nutrient concentrations as well as richness, density, basal diameter and height of trees within two plots of 14 × 14 m (392 m2) adjacent to each well. Results: Along the two gradients, groundwater levels exhibited larger fluctuations at lower than at higher elevations where the water table was deeper. Richness, density and diversity of trees decreased significantly at lower elevations where soils were waterlogged during the wet season. Soil pH and soil concentrations of carbon, nitrogen and manganese decreased significantly as elevation increased along the topographic gradients, but soil nutrient concentrations of phosphorus, aluminium and iron did not change with elevation. Groundwater samples contained only trace amounts of nutrients and were poorly correlated with elevation along the topographic gradients. Conclusions: In Neotropical savannas, the minimum distance between the soil surface and water table depth (reached during the wet season) and the relatively large fluctuations in groundwater limit tree density and diversity at low elevations as savanna trees cannot cope with extended waterlogging during the wet season and with low soil water availability during the dry season. Thus, variations of tree density and diversity along topographic gradients are more related to spatial and temporal variations in water table depth than to soil and groundwater nutrient variations in Neotropical savannas.